Sentinel Lymph Node Biopsy in Endometrial and Cervical Cancer [336]. (May 2015) - Papathomas, Daphne; Andrade, Fausto Francisco; Estape, Ricardo E.; Nasseri-Nik, Niloofar; Schroeder, Eric; Diaz, John Paul
Abstract : BACKGROUND: Sentinel lymph node biopsy is a new surgical technique for the staging of gynecologic malignancies. OBJECTIVE: To describe our experience with a modified surgical lymph node assessment of mapping and sentinel lymph node biopsy with a minimally invasive approach for cervical and uterine malignancies. METHODS: Near-infrared fluorescence imaging for robotics has been utilized at our institution since February 2013. In all cervical and endometrial cancer cases, sentinel lymph node mapping was performed with an intracervical injection of indocyanine green divided into the 3- and 9-o'clock positions before laparoscopic entry. RESULTS: A total of 32 patients were identified from February 2013 to July 2014. The median age of diagnosis was 56.5 years (range 28–77 years). The median body mass index (calculated as weight (kg)/[height (m)] 2 ) was 32.42 (range 21.6–46.2). Sentinel lymph node mapping was successful in 29 (91%) of 32 patients. A total of 75 sentinel lymph nodes were identified with a median of two sentinel lymph nodes per patient (range 0–6 sentinel lymph nodes). The majority of sentinel lymph nodes was located at two main sites, external iliac (66%) and obturator (60%). The median number of lymph nodes was 11 (range 1–34 lymph nodes). The median estimated blood loss was 50 mL (range 25–250 mL). Three patients experienced intraoperative or postoperative complications not related to the sentinel lymph node mapping. CONCLUSION: Sentinel lymph node mapping with a minimally invasive approach is feasible in newly diagnosed gynecologic malignancies. Near-infrared fluorescence imaging with intracervical indocyanine green injection using the robotic platform has a high bilateral sentinel lymph node detection rate. Sentinel lymph node mapping was successful in 91% of the cases.